The Association of Impulse Buying Behaviour with Environment and Social Factors: a Gender Perspective - Ali, Sharifah Faridah Syed
Skúmanie prepojenia environmentálnych a sociálnych faktorov, spojených s impulzívnym nákupom u mužov a žien.